Towards Homes and Graves. About the Returns, Desaparecidos and Exhumation Challenges in Peru at the End of the Twentieth Century - Pietraszczyk-Sękowska, Joanna (International Studies. Interdisciplinary Political and Cultural Journal, 2020)
The article concerns the wartime history of Peru and examines both topdown and bottom-up practices of accounting for the internal conflict of 1980–2000, which were initiated in the background of the warfare. The aim of the article is to discuss the connections I observed between the phenomena referred to in the title: return migrations of the inhabitants of the central-southern province, their search for the victims of forced disappearances, as well as the exhumation challenges emerging since the beginning of the war. In other words, the text constitutes an attempt to contextualise the above-mentioned issues given competing versions of memory about political violence in the Andes, with particular focus on their top-down determinants in the Fujimorism era.